RP-HPLC and HPTLC Estimation of Tramadol Hydrochloride and Paracetamol in Combination - Gandhimathi, M.; Ravi, T.K. (Asian Journal of Chemistry, 2010)
Two chromatographic methods for the estimation of tramadol and paracetamol were developed. RP- HPLC method used mobile phase consisted of KH2PO4 (0.1 M, pH 5.5): methanol (45:55 % v/v) and drugs monitored by UV detector. Valdecoxib was used as an internal standard. The elution order was 2.6, 5.9 and 6.5 min, respectively for paracetamol, tramadol and valdecoxib. HPTLC used a precoated silicagel G60 F254 sheets and mobile phase of ethyl acetate, toluene and ammonia and detected at 273 nm. The Rf values were 0.28 ± 0.02 and 0.57 ± 0.01 for tramadol and paracetamol, respectively. Both methods were validated as per ICH guidelines proved the suitability of the method.